EDITORIAL Connections and Divisions Across Borders - Philip, Susan (SARE: Southeast Asian Review of English, 2025)
EDITORIAL: Connections and Divisions Across Borders This farewell editorial reflects on SARE’s evolving role in connecting South, Southeast, and East Asian literatures and cultures. Highlighting articles on ecological entanglements, class oppression, transnational communities, and minority voices, it emphasizes recurring themes of unity amid division, and thanks colleagues while welcoming a new editorial team to continue SARE’s legacy.